A research project investigating the impact of digitalisation of internal business operations on organisational culture and knowledge sharing within multinational enterprises. - Dunn, Eleanor (2019)
Digitalisation is a growing priority in multinational enterprises (MNEs) to support growth, increase efficiency and remain competitive. Competition in the global economy is also driven by knowledge which has become an invaluable asset that can lead to the development of competitive advantage. The role of organisational culture in influencing knowledge sharing behaviour is already well documented in the literature which emphasises the importance of employee motivation and nurturing of a knowledge sharing culture. However, previous work has failed to explore the impact of growing digitalisation of business operations on culture and knowledge sharing within MNEs. Using Nonaka and Takeuchi’s SECI model and Hall’s iceberg theory of culture alongside Hofstede’s five dimensions of national culture and six dimensions of OC, research will be conducted to determine whether the digitalisation of the workplace influences organisational culture and the subsequent impact this has on the success of knowledge sharing within MNEs. To answer this research question, a qualitative approach is used, with semi-structured interviews and secondary data analysis as the data collection methods. The data collected was analysed using thematic analysis which was supported by the theory explored in the literature review. The findings of this study determined that use of digital technologies and platforms are increasing collaboration and promoting flexible working within MNEs which is changing perceptions towards hierarchical relationships and accessibility. This is subsequently enhancing sharing of explicit knowledge but limiting the extent of tacit knowledge sharing due to a loss of physical interaction. Results established that while changes in culture, due to digital adoption, are occurring, it is more important that MNEs nurture a culture that motivates employees to utilise technologies effectively and supports them through the change that is occurring in the digital era. By using leadership to set the example and outline expectations around technology use, employees will be better prepared for a digital future and encouraged to share their knowledge in the new and changing environment.